Analysis of the Unplugged Method in Teaching Coding and Artificial Intelligence (AI) in Grade V at SDN Kemuning - Adelia Ananda Aviva; Innany Mukhlishina (Journal of Educational Sciences, 2026)
This study examines the implementation of the unplugged method in teaching Coding and Artificial Intelligence (AI) for Grade V students at SDN Kemuning. The study is grounded in the need for learning approaches that enable elementary school students to understand abstract computational concepts through concrete and meaningful experiences without reliance on digital devices. A qualitative descriptive research design was employed, involving a classroom teacher and Grade V students as research participants. Data were collected through observations, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the unplugged method, implemented through puzzle-based activities, effectively supports students’ understanding of command flow, step-by-step sequencing, and basic computational thinking concepts. Physical and game-based activities help students visualize algorithmic processes more concretely and promote active engagement during learning. However, challenges were identified, including differences in students’ abilities, fine motor skills, and the need for longer instructional time. Teachers addressed these challenges through step-by-step guidance, intensive assistance, and reward-based motivation strategies. The study concludes that the unplugged method is a relevant and effective alternative for introducing Coding and Artificial Intelligence in elementary schools, while also fostering 21st-century skills such as critical thinking, collaboration, creativity, and problem-solving.